(untitled) (Research, Society and Development, 2020)
Objective: Discuss the repercussions of the participation of nursing students in combating the Covid-19 pandemic, considering the confrontations necessary to deal with the process of death and dying. Method: It is a reflective study, based on discursive formulations based on the critical reading of national and international publications. The text is organized into three theoretical sections: I) brief contextualization of the Covid-19 pandemic; II) aspects of nursing education in Brazil and measures implemented during the pandemic; and III) pre-existing problem: difficulties of nursing students in dealing with the process of death and dying. Results: the call of students for paid internships and the early graduation to reinforce the battle front, despite serving as experience / learning, can put students’ training, their physical and mental health at risk. It can also compromise the quality of health care and patient safety. Nursing students have difficulties to deal with the death / dying process and in the context of the pandemic, these confrontations are necessary and frequent. Final considerations: It is essential to reflect on the measures enacted by the Ministry of Health (MS) and the Ministry of Education and Culture (MEC) alerting students to the risks that will be exposed when in direct care to patients during the pandemic, including the frequent possibility of exposure to death and dying processes. Furthermore, dealing with the death / dying process during the formative process is a fundamental condition to help understand this phenomenon.